Proliferation of Local Governments in Indonesia: Identity Politics within a Troubled Nation State - Purwo Santoso (PCD Online Journal, 2017)
This article aims to scrutinise the phenomenon of proliferation of local government units in Indonesia in order to understand how identity politics has evolved within and through the process of decentralization. In doing so, there are several points to make. The numbers of districts and municipalities in Indonesia have doubled within six years. Local governments have proliferated in the sense that the numbers of local government units have multiplied rapidly in such a short period. There were 'only' a little bit more than 200 units when Suharto stepped down in 1998, and that had more than doubled to 466 units in 2006. Interestingly, this took place in an absence of a definite plan, as the state showed its enthusiasm for decentralisation and a bottom-up process of decision-making.